The Misperception of Orientation in Depth When Processing Multiple Pictures With Linear Perspective Cues. (May 2021) - Hiris, Eric; Zinnel, Laura; Rickman, Henry; Phillips, Joshua
The leaning tower illusion suggests that combining perspective cues across multiple images can affect the perceived orientation of objects in space. We measured the accuracy of orientation perception when viewing multiple pictures. Across several experiments, 11–16 participants viewed two pictures: a sidewalk and either another sidewalk, a nature scene, or no picture. Participants adjusted an on-screen line to match the remembered orientation of one of the sidewalks. Participants also made a judgment about the parallelism of the sidewalks. Sidewalks perceived as parallel were perceived to have orientations more similar to each other than when they were paired with a nature scene or no picture. The degree of misperception can be approximately twice as large as in the leaning tower illusion, and this effect survived inversion and partially survived alternating presentation of the images. The misperception was eliminated when the participants were cued on which sidewalk they would be judging; however, when forced to process both sidewalks, the misperception reappeared. We conclude that the orientation of objects with perspective cues is misperceived when viewing multiple pictures with perspective cues and this misperception appears to be related at least in part to how parallel those objects are perceived to be.